Optimization of Investigation by the Public Reserve Unit of Satreskrim to Improve the Unveiling of Criminal Acts of Theft by Weighting in the Jurisdiction of Polresta Surakarta - Budiman, Daffa Raihantra (Advances in Police Science Research Journal, 2024)
Theft by weighting is one of the most common public order disturbances that occur in Indonesia. The crime is usually committed due to the economic factors of the perpetrator. It has become a concern for the community that needs to be the primary attention of law enforcement, especially in the jurisdiction of Polresta Surakarta. In 2022, theft cases by weighting dominated compared to other criminal offenses in Polresta Surakarta. Therefore, law enforcement needs to be improved, especially in repressive efforts through investigation and prosecution. Regarding theft by weighting, the majority of obstacles faced by law enforcement occur at the investigation stage, such as not finding witnesses and evidence at the crime scene. Therefore, as the front guard in conducting investigations, the Public Reserve Unit of the Criminal Investigation Unit (Unit Resum Satreskrim) is essential in uncovering theft by weighting crimes. This research aims to analyze the organizational resources and management stages of Unit Resum Satreskrim Polresta Surakarta in optimizing investigations to increase the disclosure of criminal acts of theft by weighting. This research is a qualitative study with program evaluation and Field Research approach. Then, the source of the data is from primary and secondary data whose data is collected through interviews, observation, and document study. Furthermore, the data is confirmed using data triangulation which is then analyzed by data reduction techniques, data presentation, and drawing conclusions. The results of this study are that the organizational resources and stages of the investigation management of Unit Resum Satreskrim Polresta Surakarta have not run optimally. Therefore, problem solving is carried out in the form of participating in vocational or development education, submitting requests for personnel assistance from the sector police and other units, conducting FGD to hone skills, coordinating with other units related to borrowing infrastructure, emphasizing members regarding the correct procedure, conducting weekly evaluations, making posters related to investigation procedure, procuring a more optimal internet network, implementing a reward and punishment system, conducting kring reserse, and expanding the network of informants.